CXC Motif Chemokine Receptor 2: Glimpses into the Molecular Pathogenesis of Placenta Accreta Spectrum Disorder - Mirani, Putri; Lestari, Peby Maulina; Murti, Krisna; Liberty, Iche Andriyani; Kesty, Cindy; Andrina, Hana; Stevanny, Bella (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Investigation into the mechanism underlying excessive trophoblast invasion yields further strategies and insights for the diagnosis and treatment of placenta accreta spectrum disorder (PASD). We conducted a comprehensive literature review to analyze the relationship between CXCR2 expression and PASD, as well as the possibility of CXCR2 being used as a therapeutic and diagnostic biomarker for PASD. Chemokines are well-known mediators in the immune system, particularly for cell recruitment, angiogenesis, and tumor infiltration. CXCR2 is an important component of the immune system, particularly in neutrophils. One of the CXCR2 ligands, IL-8, has also been found to be expressed in the decidua and trophoblasts of humans and to promote autocrine or paracrine trophoblast migration and invasion. The potential role of CXCR2 in trophoblast invasion in PASD provides researchers with a glimpse into the molecular pathogenesis of PASD.CXC Motif Chemokine Receptor 2: Sekilas tentang Patogenesis Molekuler Gangguan Spektrum Plasenta AkretaAbstrakInvestigasi mekanisme invasi berlebihan trofoblas pada gangguan Spektrum Plasenta Akreta (SPA) akan memberikan lebih banyak strategi dan ide untuk diagnosis dan pengobatan. Kami melakukan tinjauan literatur yang komprehensif untuk menganalisis hubungan antara ekspresi CXCR2 dan SPA serta potensi CXCR2 sebagai penanda terapeutik dan diagnostik untuk SPA. Kemokin berperan sebagai mediator dalam sistem imun karena perannya dalam perekrutan sel, angiogenesis, dan infiltrasi tumor. CXCR2 mempengaruhi sistem imun, terutama pada neutrofil. Salah satu ligan CXCR2, IL-8, juga telah ditemukan diekspresikan dalam desidua dan trofoblas manusia serta untuk mempromosikan migrasi dan invasi trofoblas autokrin atau parakrin. Peran CXCR2 dalam invasi trofoblas pada SPA memungkinkan para peneliti untuk melihat sekilas patogenesis molekuler SPA.Kata kunci: penanda; CXCR2; plasenta akreta